Analysis of Occupational Safety, Health, and Work (K3) on Improving Employee Performance Productivity at PT. Indomarco Prismatama in Campang Raya Bandar Lampung - Nanda, Okky Riyan; Muhammad, Mahathir; Anggarini, Defia Riski (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This study aims to determine the Influence of Occupational Safety, Health, and Occupational Health (K3) on Increasing Employee Performance Productivity. Every company wants to increase the productivity of its employees' performance. Employee performance productivity is influenced by occupational safety, health, and K3. A study was conducted by PT to analyze occupational safety, health, and K3 on employee performance productivity. Indomarco Prismatama in Campang Raya Bandar Lampung. This study uses a quantitative method. The population is employees of PT. Indomarco Prismatama. The population consists of 56 employees. The sampling technique uses a census. The sample of this study was 56 employees. The data collection technique is a questionnaire. Data were analyzed by multiple linear regression. The results of this study indicate that occupational safety, health, and K3 have a significant effect on employee performance and productivity. However, these variables affect work productivity. So that PT. Indomarco Prismatama in Campang Raya Bandar Lampung can improve occupational safety, health, and K3 because these variables have a significant effect on employee performance and productivity.